2022
DOI: 10.1111/fwb.13968
|View full text |Cite|
|
Sign up to set email alerts
|

Structure and functional composition of macroinvertebrate communities in coastal plain streams across a precipitation gradient

Abstract: 1. Climate change is expected to alter rainfall and temperature regimes across the world. The hydrology and riparian zone vegetation of lotic ecosystems are tightly linked to rainfall and a mechanistic understanding of the effects of rainfall on lotic ecosystems is needed to forecast the ecological impacts of climate change.However, it is difficult to isolate rainfall effects from other environmental variables that covary across climates. To address this, we leveraged a unique steep rainfall gradient with few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…This potentially offers an explanation for climate-mediated faster recovery times (Robinson, 2012). In contrast, as discussed in Carvallo et al (2022) and observed here, taxa abundant in wetter sites including amphipods and mayflies (Cloeon spp.) are relatively slow-growing and not good dispersers; thus, would take longer to recover after a storm event.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This potentially offers an explanation for climate-mediated faster recovery times (Robinson, 2012). In contrast, as discussed in Carvallo et al (2022) and observed here, taxa abundant in wetter sites including amphipods and mayflies (Cloeon spp.) are relatively slow-growing and not good dispersers; thus, would take longer to recover after a storm event.…”
Section: Discussionmentioning
confidence: 59%
“…All sites were wadable and had a U.S. Geological Survey (USGS) flow gauge within 200 m of the sampling area. Previous work on this study system revealed that rainfall driven variation in hydrology and environmental conditions is the dominant driver of stream invertebrate community structure (Carvallo et al, 2022;Kinard et al, 2021).…”
Section: Study Areamentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, it is not surprising that the basin‐scale variables in our study explained more variance than patch‐ and reach‐scale variables. Mean daily precipitation drives the hydrological cycle and flow regime, which are the master variables in running water ecosystems (Carvallo et al, 2022; Patrick et al, 2019; Poff et al, 1997). They can affect the growth rate and, thereby, the biomass of invertebrate communities both as determinants of local conditions and through changes in systems stability.…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to localized extinctions, diminished biodiversity, and changes in community composition (Bonacina et al 2023;Eady et al 2013). Alterations in rainfall patterns and water regimes contribute to more frequent and severe droughts and floods, disrupting habitat availability and stability (Carvallo et al 2022). Drought conditions lower water flow, resulting in habitat reduction and heightened resource competition, whereas flooding can displace macroinvertebrates and erode essential habitat features.…”
Section: Challenges Faced By Macroinvertebrates In River Ecosystemsmentioning
confidence: 99%